The Influence of Customer Reviews, Working Hours, and Competition on The Number of Orders for Grabbike Drivers (Case Study on Grabbike Drivers in Malang City) - Maria Embun Intanin Jelita; Muhamad Rifa'i; Noviana Yaniar Suprajitno (International Research and Development for Human Beings (IRDH), 2026)
This study aims to examine the effects of customer reviews, working hours, and competition on the number of orders received by GrabBike drivers, both partially and simultaneously. The study employs a quantitative approach using survey data collected from 50 GrabBike drivers in Malang City through a Likert-scale questionnaire (1–5). Data analysis is conducted using multiple regression analysis, including t-tests, F-tests, and the coefficient of determination (R²). The results indicate that customer reviews have a negative and significant effect on the number of orders, while working hours have a positive and significant effect. Competition shows a positive but not significant effect on the number of orders. Simultaneously, customer reviews, working hours, and competition have a positive and significant effect on the number of orders, with a coefficient of determination of 28.1%. These findings suggest that working hours play a crucial role in increasing order volume, while the role of competition remains less influential.